An overview of the biological activities of Aristeguietia glutinosa, Lepechinia rufocampii, and Croton elegans (endemic plants of Ecuador) and its potential application in drug discovery - Tinoco Valencia, Selena Leonor (2020)
Antimicrobial resistance has generated a risk to public health, making medical treatment difficult and urgently requiring the creation of new drugs that can counteract this problem. Plants have a wide variety of secondary metabolites (phytochemicals) with biological properties capable of treating several diseases, which is why they are considered as potential candidates in drug development. In Ecuador, traditional medicine attributes to the endemic plants Aristeguietia glutinosa, Lepechinia rufocampii, and Croton elegans a great variety of therapeutic activities. However, the phytochemical and biological studies in these species are reduced, so its property as a therapeutic agent has not been fully defined. Furthermore, the families to which these species belong have an enriching history of medicinal plants, which highlights the importance of studying these plants. In this bibliographic review, the history of medicinal plants of Ecuador is briefly described with a primary focus on the recent scientific evidence on the biological activities of these three endemic species. Also, the taxonomic family to which they belong is described, highlighting the pharmacological activity of some of its most important species. Additionally, the drug discovery process is described from when the plant material is obtained until its biological activity is verified through in vitro sensitivity tests, including different methods of extraction, isolation, and characterization of the plant extract.